Isbat Nikah Siri dalam Putusan Hakim Mahkamah Syar'iyah Lhoksukan - Agustin Hanapi; Mulyadi Mulyadi; Mursyid Djawas (Sharia and Law Faculty, 2021)
Positive law only limits marriage isbat to marriages that occurred before Law no. 1 of 1974 because there is no rule requiring registration. Meanwhile, unregistered marriages that occur after the regulation cannot carry out isbat marriage, because the law only limits it before the enactment of Law no. 1 of 1974. However, the Compilation of Islamic Law provides space as Article 7 paragraph (3) letter e which reads that marriages are carried out by those who do not have marriage barriers according to Law no. 1 of 1974. Article 7 has provided a very broad absolute competence regarding isbat marriage, even though KHI is not included in the hierarchy of Legislation. Judges are given the flexibility to perform ijtihad for the benefit of all parties. This article is the basis for consideration of the Lhoksukon Syar'iyah Court judges in granting the application for isbat marriage for unregistered married couples, namely number: 131/Pdt.P/2019/MS.Lsk. number: 313/Pdt.P/2019/MS.Lsk. For this reason, this paper wants to answer the question of how the judges of the Lhoksukon Syar'iyah Court considered the reasons for the isbat of unregistered marriages, and what was the legal status of the judge's determination of the isbat of marriages for unregistered married couples. The method used is descriptive analysis method with a qualitative approach. The research approach is juridical normative and juridical sociological, using the theory of legal protection. Then use the theory of maqāṣid syarī'ah to realize goodness while avoiding evil, or take advantage and reject harm. The results of the study stated that the consideration of the judges of the Lhoksukon Syar'iyah Court in the case of isbat marriage for unregistered married couples was in accordance with the laws and regulations, the judge was also not rigid in ijtihad but considered sociological and problematic aspects.Hukum positif hanya membatasi isbat nikah pada perkawinan yang terjadi sebelum UU No. 1 Tahun 1974 karena belum ada aturan mewajibkan pencatatan. Sedangkan nikah siri yang terjadi setelah aturan itu tidak dapat melakukan isbat nikah, karena Undang-Undang hanya membatasi sebelum berlakunya UU No. 1 Tahun 1974. Namun Kompilasi Hukum Islam memberi ruang sebagaimana Pasal 7 ayat (3) huruf e yang berbunyi perkawinan yang dilakukan oleh mereka yang tidak mempunyai halangan perkawinan menurut UU No. 1 Tahun 1974. Pasal 7 ini telah memberikan kompetensi absolut yang sangat luas tentang isbat nikah, padahal KHI tidak termasuk dalam hierarki Peraturan Perundang-Undangan. Hakim diberikan keluasan untuk berijtihad demi kemaslahatan semua pihak. Pasal inilah menjadi dasar pertimbangan Majelis hakim Mahkamah Syar’iyah Lhoksukon dalam mengabulkan permohonan isbat nikah bagi pasangan nikah siri, yaitu nomor: 131/Pdt.P/2019/MS.Lsk. nomor: 313/Pdt.P/2019/MS.Lsk. Untuk itu tulisan ini ingin menjawab pertanyaan bagaimana pertimbangan Hakim Mahkamah Syar’iyah Lhoksukon terhadap alasan isbat nikah siri, dan bagaimana status hukum terhadap penetapan Hakim mengenai isbat nikah bagi pasangan nikah siri. Metode yang digunakan adalah metode deskriptif analisis dengan pendekatan kualitatif. Adapun pendekatan penelitian bersifat yuridis normatif dan yuridis sosiologis, dengan menggunakan teori perlindungan hukum. Kemudian menggunakan teori maqāṣid syarī‘ah untuk mewujudkan kebaikan sekaligus menghindarkan keburukan, atau menarik manfaat dan menolak mudarat. Hasil penelitian menyebutkan bahwa pertimbangan hakim Mahkamah Syar’iyah Lhoksukon dalam kasus isbat nikah bagi pasangan nikah siri telah sesuai dengan peraturan perundang-undangan, hakim juga tidak kaku dalam berijtihad tetapi mempertimbangkan aspek sosiologis dan masalahat.